Sorption and speciation of heavy metals in a marine clay - Lim, Teik Thye (2008)
In recent decades, the ever-increasing level of soil contamination by potentially harmful substances such as heavy metals has resulted in increasing interest in understanding the heavy metal mobility and attenuation process in soils. In this study, the capability of a marine clay to immobilise Zn, Pb, Cd, and Cu was assessed in the laboratory under acidic, neutral, and slightly alkaline conditions. The heavy metal speciation in the marine clay were investigated and their retention modes in the soil were suggested. The geoenvironmental properties of the marine clay were also assessed.